2014
DOI: 10.1007/s11605-014-2497-1
|View full text |Cite
|
Sign up to set email alerts
|

The Colon Cancer Stem Cell Microenvironment Holds Keys to Future Cancer Therapy

Abstract: Background Colorectal cancer remains the most common gastrointestinal cancer. While screening combined with effective surgical treatment has reduced its mortality, we still do not have effective means to prevent recurrence nor to treat metastatic disease. What we know about cancer biology has gone through revolutionary changes in recent decades. The advent of the cancer stem cell theory has accelerated our understanding of the cancer cell. However, there is increasing evidence that cancer cells are influenced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 61 publications
(59 reference statements)
0
28
0
Order By: Relevance
“…Ofer Reizes (Cleveland Clinic, Cleveland, OH, USA) demonstrated that leptin and leptin receptor (LEPR), a JAK/STAT cytokine receptor expressed in breast CSCs (BCSCs), are necessary for maintaining the NANOG+ BCSC phenotype (32). Dr. Emina Huang (Cleveland Clinic, Cleveland, OH, USA) showed that elevated IL-8 levels secreted from stromal fibroblasts cause a substantial increase in tumorigenicity induced by ALDH-1 + colon cancer initiating cells (CCICs) within colitis associated cancer (33). …”
Section: Microenvironment Metabolism Inflammation and New Conceptsmentioning
confidence: 99%
“…Ofer Reizes (Cleveland Clinic, Cleveland, OH, USA) demonstrated that leptin and leptin receptor (LEPR), a JAK/STAT cytokine receptor expressed in breast CSCs (BCSCs), are necessary for maintaining the NANOG+ BCSC phenotype (32). Dr. Emina Huang (Cleveland Clinic, Cleveland, OH, USA) showed that elevated IL-8 levels secreted from stromal fibroblasts cause a substantial increase in tumorigenicity induced by ALDH-1 + colon cancer initiating cells (CCICs) within colitis associated cancer (33). …”
Section: Microenvironment Metabolism Inflammation and New Conceptsmentioning
confidence: 99%
“…This cell population is not stationary, but can be transformed from mesenchymal cells, endothelial cells, adipose cells and even cancer epithelial cells. CAFs promote tumor progression and invasion by both mechanical forces and metabolic machinery (113). On the one hand, CAFs induce protease-mediated extracellular matrix remodeling, serving to guide the structures that direct migration (114).…”
Section: Microenvironment-mediated Self-renewal Of Ccscsmentioning
confidence: 99%
“…In addition to the above mentioned, others, such as blood vessels, microorganisms and normal cells, all exert an influence on the micro-environment (113,138). All of these complex components interact with each other to regulate CCSC self-renewal.…”
Section: Inflammation Factorsmentioning
confidence: 99%
“…The IBD patients have an increased risk to develop inflammation-associated colon cancer. Additionally, during repair and regeneration of damaged epithelium in IBD patients, there might be an increased chance of mutation accumulation (cyclic hit model, described in later paragraphs), and the metaplastic Paneth cells may contribute to accelerated epithelial tumorigenesis by providing stem cell growth factor to tumor cells (Chen and Huang, 2014).…”
Section: Metaplastic Paneth Cells In Colon and Its Disease Relevancementioning
confidence: 99%